Drivers of nest survival rate in a southern Tunisian population of Laughing Doves (Spilopelia senegalensis) - Jihen Boukhriss (Avian Research, 2019)
Abstract Background Investigating the ecological factors and processes shaping nest survival is of great importance for assessing the breeding success of bird populations and understanding their spatio-temporal dynamics. Here, this question is addressed for the Laughing Dove (Spilopelia senegalensis), an expanding Afro-tropical bird in the Tunisian oasis habitat. Methods This study took place in Kettana oasis, in south-eastern Tunisia. Natural Laughing Dove nests were searched for and monitored by means of regular visits, from the discovery date until the end of the breeding attempt (i.e. fledging or failure). Data were then used to investigate the relevance of laying date, nest age (days after clutch initiation), nest height and vegetation structure in the close nest tree environment as predictors of daily nest survival rate, using logistic-exposure models that accounted for heterogeneity in monitoring period among the studied nests. Models including different combinations of covariates were ranked according to their AICc scores, and the model-averaging technique was used for the assessment of the effects of covariates on daily nest survival rate. Results Vegetation structure in the close nest tree environment and nest age provided important predictors of daily nest survival rate, whereas neither nest height nor laying date showed significant effects. Daily nest survival rate was negatively associated with the presence of date palm trees in the close nest tree environment, but it was positively related to nest age. Daily nest survival rate was higher during the post-hatching stage than during the pre-hatching stage. Conclusions Nests placed on fruit trees close to clumps of palm trees suffered higher predation risks compared to those placed on fruit trees situated far from palm trees. This is probably because palm tree clumps provided refuges for nest predators, notably the Black Rat (Rattus rattus) which has been reported to be the main nest predator in the oasis habitat. The predatory activity of this rodent seemed more directed against eggs than nestlings, which may explain the observed increase in daily survival rate with nest age.